Na styku mediów, na styku technik. „Foto-grafia” klasyczna i cyfrowa w polskiej poezji najnowszej - Englender, Barbara (Przestrzenie Teorii, 2022)
The aim of this text is to present the literary image of the breakthrough that occurred with the invention of digital photography. The article focuses on the most contemporary Polish poetry – mainly authors born in the 70s, such as Jacek Dehnel, Marcin Świetlicki or Bronka Nowicka. On the basis of their texts, the literary image of both traditional analog photography and photos created with the use of the latest techniques is reconstructed. In her interpretations, the author uses the tools she has developed herself, which include concepts such as “photo-graphemicality”, which is a combination of features linking text with photography, and “photo-grapheme”, which is its individual realisation.